2023
DOI: 10.1177/02698811221144635
|View full text |Cite
|
Sign up to set email alerts
|

We need to talk: The urgent conversation on chronic pain, mental health, prescribing patterns and the opioid crisis

Abstract: The opioid crisis’ pathways from first exposure onwards to eventual illnesses and fatalities are multiple, intertwined and difficult to dissect. Here, we offer a multidisciplinary appraisal of the relationships among mental health, chronic pain, prescribing patterns worldwide and the opioid crisis. Because the opioid crisis’ toll is especially harsh on young people, emphasis is given on data regarding the younger strata of the population. Because analgesic opioid prescription constitute a recognised entry poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 141 publications
2
4
0
Order By: Relevance
“…There are indications that exposure to childhood trauma may increase the risk of persistent pain, although most studies on the subject assess childhood trauma retrospectively, 21 , 63 possibly introducing bias, 20 , 45 and prospective findings are conflicting. 43 , 59 , 60 Trauma reactions such as sleep disturbances, hypervigilance, and avoidance are symptoms considered to be relevant for the maintenance and exacerbation of pain conditions, 7 , 10 , 38 , 51 , 53 , 56 and our finding that post-traumatic stress symptoms were related to higher prescription rates in young adulthood among trauma-exposed participants aligns with this. Childhood interpersonal trauma is considered a predisposing factor for alterations in pain signaling leading to chronic pain.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…There are indications that exposure to childhood trauma may increase the risk of persistent pain, although most studies on the subject assess childhood trauma retrospectively, 21 , 63 possibly introducing bias, 20 , 45 and prospective findings are conflicting. 43 , 59 , 60 Trauma reactions such as sleep disturbances, hypervigilance, and avoidance are symptoms considered to be relevant for the maintenance and exacerbation of pain conditions, 7 , 10 , 38 , 51 , 53 , 56 and our finding that post-traumatic stress symptoms were related to higher prescription rates in young adulthood among trauma-exposed participants aligns with this. Childhood interpersonal trauma is considered a predisposing factor for alterations in pain signaling leading to chronic pain.…”
Section: Discussionsupporting
confidence: 83%
“…This study was conducted in a geographical region without metropolitan areas and with low immigration 39 ; however, previous studies have found similar rates of long-term opioid use regardless of such characteristics. 58 Although health care is highly accessible and affordable in Norway, the associations revealed in this study seem to conform with patterns found in populations with different health care systems, 6,7,58,64 and we therefore consider that these associations may be generalized to other populations. The universal mechanisms outlined above also supports the generalizability of results across populations with different prescription rates.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations